Alternative fuels and sustainable mobility: is the future road paved by biofuels, electricity or hydrogen?. (23rd April 2007) - G. Hoyer, Karl; Holden, Erling
This paper compares 16 alternative energy chains in a Well-to-Wheel analysis including three indicators: energy use, emissions of climate gases and emissions of local/regional pollutants. The analysis includes a private car which uses natural gas, biological fuels, electricity and hydrogen, respectively. The analysis shows that an alternative which scores favourably on one indicator often scores unfavourably on other indicators. Sustainable mobility, however, requires favourable scores on all indicators. Thus, sustainable mobility must combine three different approaches: the efficiency approach which includes the use of alternative energy the substitution approach and the reduction approach.